Usefulness of cytological specimens from bronchial brushings and bronchial washings in addition to endobronchial biopsies during bronchoscopy for lung cancer: 3 years data from a chest clinic in a general hospital - Abdul Rani, Mohammed Fauzi; Balakrishnan, L.; Rathor, Mohammad Yousuf (Malaysian Medical Association, 2003)
retrospective review of all bronchoscopy cases for investigation of lung cancer between January 1997 and December 1999 was done. The cases were included if endobronchial mass was visible (Group A) or when there was an abnormal mucosa and/or bronchial narrowing in the absence of a mass (Group B). All patients in Group A (n = 177) underwent endobronchial biopsy (EB) bronchial brushings (BB) and bronchial washings (BW). All cases in Group B underwent transbronchial biopsy (TBB), BB and BW. Only a small increase in the positive results for cancer was seen when cytology specimens (BB and BW) were added to EB (85.3% vs 88.1%, McNemar's P = 0.06) in Group A but there was a significant increase in Group B (37.3% vs 54.2%. McNemar's, P = 0.001). Therefore although cytology specimens did not significantly add to overall yield of positive results when endobronchial lesions were visible, when mass lesions were not visible, cytology specimens increased the yield by 16.9%.